Challenges for the education of children and youth in the 21st Century - Latorre Ariño, Marino (2021)
The great newness of our time is that the world has not only changed but is in a situation of accelerated change. The society that was coming has already arrived, the future has arrived, and it is called uncertainty. Students need to develop competencies such as creativity, autonomy, flexibility, and entrepreneurship. We do not know what society will be like in 20 or 30 years, so we ask ourselves: How are we going to educate today's students for a society that does not yet exist? The answer is given by Morin, (1999): Knowledge is being able to navigate the ocean of uncertainty supported by archipelagos of certainties (p. 43). What are these certainties? A set of values-attitudes and abilities-skills that help students to make decisions in their lives that allow them to learn and keep learning throughout their lives, becoming honest and solidary citizens. This challenge must be assumed by the student, the family, and the school. Providing educational models and curricular designs that make it possible to achieve this goal is an excellent and necessary contribution for the school. This article presents the socio-cognitive-humanist paradigm as an updated and modern form of pedagogical intervention. It also presents a reflection on education and its evangelizing function in the Catholic school, in order to meet the educational and evangelizing demands of today's society from the point of view of the Marist educational mission.